2002
DOI: 10.1080/01446190210159908
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the global construction industry: improving the quality of data

Abstract: In the context of a truly global market for construction, an international strategy is required to ensure that national and international statistical systems are able to provide accurate and valid information. In many parts of the world the collection of reliable national information on construction activity is not an easy task, and the measurement of comparable, cross-national data can be problematic. This paper considers possible strategies for the improvement of data collection systems in the context of use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…These offices, being public in nature, are often wanting in terms of quality of services. For that matter, Ruddock (2002) has emphasized the need to improve the national statistical systems. Statistics are always collected and compiled about it along with other sectors of the national economy.…”
Section: Constructing Construction Statisticsmentioning
confidence: 99%
“…These offices, being public in nature, are often wanting in terms of quality of services. For that matter, Ruddock (2002) has emphasized the need to improve the national statistical systems. Statistics are always collected and compiled about it along with other sectors of the national economy.…”
Section: Constructing Construction Statisticsmentioning
confidence: 99%
“…These offices, being public in nature, are often wanting in terms of quality of services. For that matter, Ruddock (2002) has emphasized the need to improve the national statistical systems. It is against this background that the Kenyan system is being reformed.…”
Section: Conceptual Challenges To Statistical Frameworkmentioning
confidence: 99%
“…A CIB TG31 Survey reported in Ruddock (2002) found that non-public agencies are greatly involved in the production of statistics on the construction sector at national levels. A comprehensive information system integrating both public and non-public producers therefore needs to be put in place along the lines suggested by Ofori (1988).…”
Section: Conceptual Challenges To Statistical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors (Ruddock, 2000(Ruddock, & 2002Ruddock and Lopes, 2006) indicated the limitations of this approach and suggested that time series statistics of one country, rather than cross-sectional data across countries, was a more effective approach to permit the identification of trends. In a further study, Lopes et al (2002) applied these recommendations to developing countries in subSaharan Africa.…”
Section: Introductionmentioning
confidence: 99%